Pengembangan E-Book Cibubaba (Cinta Budaya Bangkalan Bersama) Berbasis Flipped Classroom Materi Warisan Budaya Mata Pelajaran IPAS Muatan IPS Kelas V UPTD SDN Pamorah - Nur Aida; Andika Adinanda Siswoyo (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Issues identified at UPTD SDN Pamorah Bangkalan include students' limited understanding of local culture, a scarcity of contextual teaching materials for the IPAS (Natural and Social Sciences) subject, and minimal use of digital technology in instruction. These conditions highlight the need to develop innovative teaching materials that integrate local wisdom with a technology-based learning approach. This study aimed to examine the validity, effectiveness, and attractiveness of the Cibubaba (Cinta Budaya Bangkalan Bersama) E-book, which was developed using a flipped classroom approach for cultural heritage topics in Grade V Social Studies content within the IPAS subject. The research employed a Research and Development (R&D) method based on the 4D model, consisting of the stages of define, design, develop, and disseminate. The participants included three expert validators, one fifth-grade teacher, and 37 students. Data were gathered through interviews, observations, questionnaires, tests, and documentation. The findings revealed that: (1) the validity assessment of the Cibubaba. E-book resulted in scores of 90% from the teaching material expert, 88% from the instructional design expert, and 93.3% from the subject matter expert, indicating a highly valid category; (2) the effectiveness of the E-book was reflected in teacher activity and student activity scores of 100% and 98%, respectively, while classical learning mastery exceeded the 85% criterion; and (3) the attractiveness aspect achieved scores of 90% based on teacher responses and 90.16% based on student responses, both categorized as highly attractive. Therefore, the flipped classroom-based Cibubaba E-book can be considered valid, effective, and appealing for implementation in elementary school learning activities.